Pengaruh Media Sosial terhadap Pola Pengeluaran dan Manajemen Keuangan Mahasiswa - Raja, Fitra Aulia; Rhoma Iskandar; Tanjung, Boma Jonaldy (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of social media on students’ spending patterns and financial management. This research employed a quantitative approach with a causal-associative design. The population consisted of undergraduate students of the Management Study Program at Panca Sakti University, Bekasi. A total of 119 respondents were selected as the final sample using the Isaac and Michael formula. Data were collected through a Likert-scale questionnaire and analyzed using multivariate linear regression with IBM SPSS version 26. The results indicate that social media does not have a statistically significant effect on students’ spending patterns (Sig. = 0.696) or financial management (Sig. = 0.247). The multivariate test also shows no simultaneous significant effect on both dependent variables. However, the coefficient of determination reveals that social media explains 31.7% (R² = 0.317) of the variance in spending patterns and 5.0% (R² = 0.050) of the variance in financial management, indicating a limited explanatory power. Although social media does not significantly influence students’ spending patterns and financial management, it still contributes to variations in students’ financial behavior. This study is limited to one university and one cohort, which may restrict the generalizability of the findings. The findings provide empirical evidence for future research and serve as a reference for developing financial literacy programs among students.